(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
The impact of scintillation on radio communications, geodesy, radar system and navigation cannot be underemphasized. The first evident effect of space weather in the phase of radio signals and amplitude that passes over ionosphere is fluctuations. If there are intense fluctuations in the quality of the signals received, such signals might degrade or attenuate in quality. This phenomenon is referred to as scintillations. To study the effects of magnetic activity on scintillations, the percentage occurrence of scintillations has been separated for the five international quiet (Q) days and five international disturbed (D) days over Ilorin for the year 2012 which was obtained from world data centre Kyoto. The occurrences of S4 were recorded during quiet days than the disturbed days in the study area. Generally, occurrence of \(S_4\) was enhanced during pre-midnight hours but was suppressed during post-midnight hour both at quiet and disturbed days in Ilorin, Kwara State, Nigeria.